The semantics of metaphor and parable: Looking for meaning in the Gospels - Wierzbicka, Anna (Theoria et Historia Scientiarum, 2007)
Human communication relies largely on metaphors. This applies to literature, to politics, to everyday interaction, to religion and to ethics. Indeed we live by metaphors, as the title of the well-known book by Lakoff and Johnson (1980) suggests. Yet despite their vital importance the meaning of metaphors is often far from clear - even to those who use them. The problem is compounded in cross-cultural communication, because while the letter of the metaphor can often be translated, the translated version may be baffling or deceptive.